2019
DOI: 10.1074/jbc.ra119.008879
|View full text |Cite
|
Sign up to set email alerts
|

Error-prone replication of a 5-formylcytosine-mediated DNA-peptide cross-link in human cells

Abstract: Edited by Patrick Sung DNA-protein cross-links can interfere with chromatin architecture, block DNA replication and transcription, and interfere with DNA repair. Here we synthesized a DNA 23-mer containing a sitespecific DNA-peptide cross-link (DpC) by cross-linking an 11-mer peptide to the DNA epigenetic mark 5-formylcytosine in synthetic DNA and used it to generate a DpC-containing plasmid construct. Upon replication of the DpC-containing plasmid in HEK 293T cells, approximately 9% of progeny plasmids contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…TLS polymerases have been shown to bypass a GSH-based adduct ( 52 , 69 , 70 ) and (N-terminal-linked) peptides as long as 5- and 12-mers ( 71 , 72 , 73 ) but not a 23-mer peptide or green fluorescent protein ( 72 ). In vitro studies, including some in cells, have shown the mutagenic bypass of DNA–peptide cross-link by TLS polymerases ( 11 , 42 , 74 ). It is important to know how a DNA polymerase can bypass each cross-linked peptide entity and potentially cause base-pair mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLS polymerases have been shown to bypass a GSH-based adduct ( 52 , 69 , 70 ) and (N-terminal-linked) peptides as long as 5- and 12-mers ( 71 , 72 , 73 ) but not a 23-mer peptide or green fluorescent protein ( 72 ). In vitro studies, including some in cells, have shown the mutagenic bypass of DNA–peptide cross-link by TLS polymerases ( 11 , 42 , 74 ). It is important to know how a DNA polymerase can bypass each cross-linked peptide entity and potentially cause base-pair mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian TLS polymerases include Y-family Pol η, ⍳, and κ and Rev1 ( 41 ), which have low processivity and fidelity ( 39 ). Only in a few cases has the mutagenic potential of a DNA–peptide cross-link been analyzed ( 42 ), and essentially all of the work in this area has been done with either uncharacterized cross-links or synthetic models.…”
mentioning
confidence: 99%
“…Early studies from the Lloyd laboratory showed that bacterial DNA polymerases could efficiently bypass 4-mer- and 12-mer peptides linked to DNA by a ring-opened γ-hydroxypropano dG adduct ( 47 , 48 ). Since then, several studies have been done with human TLS polymerases that can bypass DNA–peptide cross-links ( 19 , 49 , 50 ), although the number of reports is relatively small. However, these have involved shorter peptides (10-mers), and in one study a 23-mer posed a strong block to replication by hpol η, ι, and κ ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Pol ι has been shown to be able to bypass bulky adducts that are unable to be bypassed by other translesion synthesis (TLS) polymerases (74). Furthermore, in the presence of Mn 2+ , Pol ι is able to bypass a peptide adduct that mimics the DNA-protein crosslink repair intermediate (75,76). This ability may constitute an effective alternative in countering the accumulation of crosslinking damage from FA pathway loss.…”
Section: Discussionmentioning
confidence: 99%